2007
DOI: 10.7773/cm.v33i2.1055
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the population structure of jumbo squid (Dosidicus gigas) in Santa Rosalía, central Gulf of California

Abstract: El calamar gigante Dosidicus gigas (D'Orbigny 1835) es una especie endémica del Océano Pacífico oriental que se distribuye aproximadamente entre 40ºN y 45ºS (Nigmatullin et al. 2001). Constituye un importante recurso pesquero en el Golfo de California (Ehrhardt et al. 1983, Morales-Bojórquez et al. 2001), en la región del domo de Costa Rica (Ichii et al. 2002) y frente a las costas de Perú y Chile (Taipe et al. 2001). Dosidicus gigas es un componente importante dentro del ecosistema del Golfo de California ya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
15
1
4
Order By: Relevance
“…7), which could indicate the periodicity of arrival of new specimens to the fishing area. The sex ratio obtained for the entire fishing period showed an apparent dominance of D. gigas males over females, which is the opposite of what has been reported in previous studies from the Gulf of California (Markaida & Sosa-Nishizaki 2001, Bazzino et al 2007) and Peruvian waters (Tafur et al 2001, Tafur et al 2010. This condition could be the product of the selective effect of the jigs when specimens are immature or the product of spatial segregation and migration between sexes in the study area.…”
Section: Fourier Series Analysiscontrasting
confidence: 79%
See 1 more Smart Citation
“…7), which could indicate the periodicity of arrival of new specimens to the fishing area. The sex ratio obtained for the entire fishing period showed an apparent dominance of D. gigas males over females, which is the opposite of what has been reported in previous studies from the Gulf of California (Markaida & Sosa-Nishizaki 2001, Bazzino et al 2007) and Peruvian waters (Tafur et al 2001, Tafur et al 2010. This condition could be the product of the selective effect of the jigs when specimens are immature or the product of spatial segregation and migration between sexes in the study area.…”
Section: Fourier Series Analysiscontrasting
confidence: 79%
“…A significant interannual variability was also observed in the population structure of jumbo squid in the Gulf of California (Markaida 2006, Neva´rez-Martı´nez et al 2006, Bazzino et al 2007). Genetic and phenotypic plasticity have been mentioned as possible sources of differences in maximum size (Nesis 1983, Keyl et al 2008.…”
Section: Introductionmentioning
confidence: 83%
“…At the same time, landings of jumbo squid have greatly increased (IMARPE unpubl. data: see also FAO ftp://ftp.fao.org/FI/STAT/summary/ a1e.pdf). Temporal variation in size-at-maturity has also been observed in the northern hemisphere, although in a different form; here jumbo squid generally matured at large sizes (at least since the late 1980s), and only during the El Niño event of 1997/1998 did size-at-maturity drop to sizes similar to those found in Peru during the early 1990s (Markaida 2006b, Bazzino et al 2007). However, small specimens were also reported from Mexican waters in the 1970s and the 1980s ( Table 1).…”
Section: Introductionmentioning
confidence: 88%
“…Mar Ecol Prog Ser 400: [127][128][129][130][131][132][133][134][135][136][137][138][139][140][141] 2010 tive biology (Markaida 2006b, Argüelles et al 2008, as well as population structure in general (Bazzino et al 2007). Analyzing size-at-maturity of females of the Peruvian exclusive economic zone only, a transition period lasting from 1999 to 2000 was identified that separates a period of small mature females in the 1990s from the period of large mature females in the 2000s (Argüelles et al 2008).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation